Supply Chain Management in the Indonesian Fashion Industry and Analysis of Corporate - Aripin Ahmad (International Journal of Supply Chain Management, 2018)
The purpose of the study is to determine the role of risk and performance on maintaining the SSCM level, to regulate the role of sustainable supply chain management on maintaining the sustainable product, to discuss the mediating role of SSCM between the role of risk and performance and the sustainable product and to examine the role of PLS assessment product on maintaining the sustainable product. Through e-mail survey has been chosen, and questionnaires has been dispersed by using simple random sampling method. The three hundred (300) questionnaires has been dispersed among fashion industry model of Indonesia. The result shown that Risk and Performance, SSCM and PLC Assessment possess a positive association on Sustainable Product. Further, the results of the investigation uncover that these organizations in Indonesia center altogether around provider consistence with their set of accepted rules, utilizing further checking and inspecting exercises to avert production issues in creating nations, enhance generally sustainability criteria and supply chain performance for their providers.